America in the British imagination : 1945 to the present / John F. Lyons. - Lyons, John F., 1960- (Palgrave Macmillan, 2013)
This lively and engaging cultural history explores a series of interrelated questions about the US's influence on British society in the years following World War II. How was American culture disseminated into Britain? Why did large sections of British society embrace American customs? What picture did British citizens form of American society and politics? And how did the Cold War's end and the September 11 attacks affect that picture?